TECHNICAL EDUCATION IN BASIC SCHOOLS - HISTORY AND PRESENT - SERAFIN, Cestmir; HAVELKA, Martin; KROPAC, Jiri (Journal of Technology and Information Education, 2018)
This paper deals with the context of changing the concept of technical education at basic schools. There will be analysed broader context of process in preparing students at basic schools in the field of technical oriented subjects in 20th and 21st century within the area of the current Czech Republic. In the paper, there is presented a research describing the current situation in the area technical education in schools at Olomouc region.
Keywords: Technical education; craft; basic school; pedagogy; technology; teaching; education; training